2005
DOI: 10.1186/bcr1174
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles and the TP53 mutation status are powerful prognostic markers of breast cancer

Abstract: There is compelling evidence from transgenic mouse studies and analysis of mutations in human carcinomas indicating that the TGF-β signal transduction pathway is tumor suppressive. We have shown that overexpression of TGF-β1 in mammary epithelial cells suppresses the development of carcinomas and that expression of a dominant negative type II TGF-β receptor (DNIIR) in mammary epithelial cells under control of the MMTV promoter/enhancer increases the incidence of mammary carcinomas. Studies of human tumors have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
131
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(153 citation statements)
references
References 0 publications
16
131
1
5
Order By: Relevance
“…Our data suggest that loss of p53 (by inactivation or mutation), one of the most common events occurring in cancer, might contribute to the upregulation of Cdc25B observed in many types of tumors. In agreement with this, Cdc25B was identified in a set of genes more highly expressed in primary breast tumors with p53 mutations (Troester et al, 2006;Langerod et al, 2007). As many p53 mutants not only act through dominant-negative function but also acquire a gain-of-function, notably by enhancing the activity of NF-Y (Di Agostino et al, 2006), the increased expression of Cdc25B in mutant p53 tumors (Troester et al, 2006;Langerod et al, 2007) may stem not only from loss of WT p53 repressive activity but also from the gain of functional properties of the mutant protein.…”
Section: Cdc25b Is Negatively Regulated By P53 M Dalvai Et Alsupporting
confidence: 67%
“…Our data suggest that loss of p53 (by inactivation or mutation), one of the most common events occurring in cancer, might contribute to the upregulation of Cdc25B observed in many types of tumors. In agreement with this, Cdc25B was identified in a set of genes more highly expressed in primary breast tumors with p53 mutations (Troester et al, 2006;Langerod et al, 2007). As many p53 mutants not only act through dominant-negative function but also acquire a gain-of-function, notably by enhancing the activity of NF-Y (Di Agostino et al, 2006), the increased expression of Cdc25B in mutant p53 tumors (Troester et al, 2006;Langerod et al, 2007) may stem not only from loss of WT p53 repressive activity but also from the gain of functional properties of the mutant protein.…”
Section: Cdc25b Is Negatively Regulated By P53 M Dalvai Et Alsupporting
confidence: 67%
“…The presence of mutated p53 was associated with patient characteristics of increased age and postmenopausal status, and tumor characteristics of ductal morphology, higher grades and ER/PR negativity, in agreement with previous studies [5,34,35]. The highest rates of mutations were seen in the HER2 and triplenegative subtypes, as reported in other studies [12,36,37]. Most mutations were found at classical hotspot codons and were loss of function mutations as assessed in yeast functional assays [17].…”
Section: Discussionsupporting
confidence: 78%
“…A reported alternative for identification of 'functional' loss of wild-type p53 is a p53 transcriptional fingerprint. Several gene expression signatures have been reported that distinguish between wild-type and mutant p53 [36,43,44]. Interestingly some TP53 wild-type tumors expressing the mutation-associated 32-gene signature behaved aggressively, while some TP53 mutant tumors lacking the signature had favorable outcome [43].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with molecularly defined luminal B tumors show highest mortality after 5-8 years. 22 Late relapse of the latter subtype may be triggered by discontinuation of endocrine therapy or may reflect its natural history and intrinsic aggressiveness. As such, there is a clear need to prospectively identify patients with luminal B cancers, particularly those in the lymph node-negative category, who may benefit from adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…39 TP53 alterations whether detected by molecular or immunohistochemical assays have been shown to be a marker of poor prognosis and to be predictive of treatment response by some but not all investigators. 7,12,15,22,38 Of note, when we substituted either PR or TP53 for Ki67 marked variation was seen in the distribution of the luminal subgroups with associated poor kappa statistics. These findings indicate that the three methods employed in this study identified different patients as being of poor prognosis, thereby limiting the clinical utility of the Ki67 classification alone.…”
Section: Lp Feeley Et Almentioning
confidence: 99%